2010
DOI: 10.1136/bjo.2010.180422
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of histamine-induced conjunctival oedema in guinea pigs by means of image analysis

Abstract: This is the first study to have quantitatively evaluated kinetic changes in histamine-induced bulbar oedema by means of image analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 16 publications
0
10
0
Order By: Relevance
“…This study was approved by the Animal Care Committee of Kochi Medical School (K-00118), and the procedures were performed according to the guidelines of the Association for Research in Vision and Ophthalmology Statement for the use of Animals in Ophthalmic and Vision Research . In vivo performance analysis of the EH-SCL was performed based on the previously reported animal model of allergic conjunctivitis [12]. In this animal model, the immediate phase of allergic conjunctivitis is induced by histamine eye drops, and the magnitude of the allergic reaction is measured by the extravasated EB, which was injected intravenously before the histamine challenge.…”
Section: Methodsmentioning
confidence: 99%
“…This study was approved by the Animal Care Committee of Kochi Medical School (K-00118), and the procedures were performed according to the guidelines of the Association for Research in Vision and Ophthalmology Statement for the use of Animals in Ophthalmic and Vision Research . In vivo performance analysis of the EH-SCL was performed based on the previously reported animal model of allergic conjunctivitis [12]. In this animal model, the immediate phase of allergic conjunctivitis is induced by histamine eye drops, and the magnitude of the allergic reaction is measured by the extravasated EB, which was injected intravenously before the histamine challenge.…”
Section: Methodsmentioning
confidence: 99%
“…Disruption of the blood-tear barrier is also described in human patients with spontaneous ocular surface disorders (e.g., dry eye, allergic conjunctivitis) 226,305-307 and other animal species (rabbits, horses, and guinea pigs). 164,308,309 Increased vascular permeability and disruption of tight junctions between conjunctival epithelial cells likely play a role ( Figure 6), 310,311 although the exact etiopathogenesis is unknown and require further investigation. A few noteworthy limitations are listed here: (i) the model is not adequate to study ocular allergy given the lack of characteristic features noted in canine patients with allergies (e.g., follicular conjunctivitis); (ii) proinflammatory mediators other than histamine are also responsible for triggering conjunctival inflammation in clinical patients (e.g., leukotrienes, cytokines); (iii) conjunctival inflammation is relatively short-lived (115-390 min) and cannot mimic the physiological changes noted in patients with chronic conjunctivitis (e.g., reduced goblet cell density).…”
Section: Histamine-induced Conjunctivitismentioning
confidence: 99%
“…Earlier, Fukushima and Tomita [21] and Takahashi et al [22] reported that image analyses can be used to quantitatively evaluate the conjunctival hyperaemia and oedema in guinea pigs with histamine-induced hyperaemia or an allergic reaction. However, their methods cannot be easily used in humans because they require the injection of histamine.…”
Section: Discussionmentioning
confidence: 99%